Why Firms Avoid Cutting Wages : Survey Evidence from European Firms - Du Caju, Philip; Kosma, Theodora; Lawless, Martina; Messina, Julian; Room, Tairi (World Bank Group, Washington, DC, 2014)
Firms very rarely cut nominal wages, even in the face of considerable negative economic shocks. This paper uses a unique survey of fourteen European countries to ask firms directly about the incidence of wage cuts and to assess the relevance of a range of potential reasons for why the firms avoid cutting wages. The paper examines how firm characteristics and collective bargaining institutions affect the relevance of each of the common explanations put forward for the infrequency of wage cuts. Concerns about the retention of productive staff and a lowering of morale and effort were reported as key reasons for downward wage rigidity across all countries and firm types. Restrictions created by collective bargaining were found to be an important consideration for firms in Western European (EU-15) countries but were one of the lowest ranked obstacles in the new EU member states in Central and Eastern Europe.